The effect of mangosten (garcinia mangostana l.) shell extract on quality changes of fresh catfish (pangasius hypophthalmus) stored at room temperature - Afsri Rahmadanis; Sukirno '; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate the quality change of fresh catfish added with mangosteen ( Garcinia mangostana L.) shell extract and stored at room temperature. The fish weighing 300-400 g each was taken from a fish market in pekanbaru. The fish was eviscerated, washed and grouped into 3 groups. Each group was swabed with mangosteen shell extract at a level of 0%, 2% and 4% of fish weight. Quality of catfish was evaluated for sensory quality, bacterial count, pH and Staphylococcus aureus at 0, 3, 6, 9, 12 and 15 hours. The result showed that the catfish swab with 4% of mangosteen shell extract was the best in shelf life which was still acceptable up to 12 hours. The pH value at the first increased from 6,43 at initial storage to 7,26 at 12 hours storage (spoilage). Bacterial count increased from 2,8 x 104 colonis/g at initial storage to 4,8 x 105 colonis/g at 12 hours storage (spoilage). There was no Staphylococcus aureus during storage.Keywords: mangosteen shell extract, catfish, quality ch